Notes on chydorid endemism in continental Africa: Matralona gen. n., a monotypic Alonine from the Fouta Djalon Plateau (Guinea, West Africa) (Crustacea: Cladocera: Anomopoda) - van Damme, Kay; Dumont, Henri J. (Zootaxa, 2009)
A study of the morphology of Alona simonei Dumont, 1981, here emended to Alona simoneae, from the ancient Fouta Djalon Plateau in Guinea (West Africa) reveals unique limb structures. We allocate this species to the monotypic Matralona gen. n. and consider it a relict of an Alona-like clade. Matralona gen. n. is another example of divergence in limb morphology among externally similar Aloninae. Separation of this monotypic genus is based on more than autapomorphies alone and we include arguments for significant isolation from the ancestral stock. Within the Aloninae, Matralona gen. n. shows closest affinities with the Australasian genus Armatalona Sinev, 2004. Both taxa may share a common ancestor. Matralona gen. n. is one of the most peculiar African Chydoridae with no close relatives on the continent. We discuss a few areas of endemism in Chydoridae that begin to emerge on continental Africa.